The activity prediction of indole inhibitors against HCV NS5B polymerase. (13th November 2019) - Muhire, Jules; Zhai, Hong Lin; Lu, Shao Hua; Li, Sha Sha; Yin, Bo; Mi, Jia Ying
Abstract: Non‐structural viral protein 5B (NS5B) is a viral protein in hepatitis C virus. Although various inhibitors against NS5B have been found, the activity prediction of similar untested inhibitors is still highly desirable. In this respect, the Tchebichef moments (TMs) calculated from the images of molecular structures were regarded as the independent variables while the inhibitory activity (pIC50 ) was the dependent variable, and the predictive model was established by means of stepwise regression. The R ‐squared of leave‐one‐out cross‐validation ( Q 2 ) for the training set and the R ‐squared of prediction ( R p 2 ) for external independent test set were 0.919 and 0.927, respectively. The obtained model was also evaluated strictly. Compared with the multivariate curve resolution with alternating least squares (MCR‐ALS) and the QSAR approaches derived from the literature, the proposed method is more accurate and reliable. This study not only provides an effective approach to predict the biological activity of RNA replication's inhibitors, but also extends the QSAR modeling technique. Abstract : The process of predicting the activity from molecular structures.